2018
DOI: 10.1159/000492324
|View full text |Cite
|
Sign up to set email alerts
|

Association between Thyroid-Stimulating Hormone Levels and Non-Alcoholic Fatty Liver Disease Is Not Independent from Metabolic Syndrome Criteria

Abstract: Introduction: Thyroid hormones are involved in the regulation of body composition, lipid metabolism, and insulin resistance. Thus, it is possible that they might play a role in the pathogenesis of non-alcoholic fatty liver disease (NAFLD). However, the role of thyroid function on NAFLD is not well defined. In this study, we evaluated the relationship between thyroid-stimulating hormone (TSH) levels, within the reference range, and presence of NAFLD in asymptomatic individuals. Study Design: We included all ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…What’s more, results in a large longitudinal cohort study showed that the correlation of TSH with MAFLD was not independent of cardiometabolic confounders ( 32 ). Another study involving 10,539 individuals suggested that the association between TSH and MAFLD was mediated by the characteristics of MetS (waist circumference, HDL levels, triglycerides levels, DM, and systemic arterial hypertension) ( 33 ). Notably, an inverse correlation between FT4 level and risk were found in some studies ( 12 , 29 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…What’s more, results in a large longitudinal cohort study showed that the correlation of TSH with MAFLD was not independent of cardiometabolic confounders ( 32 ). Another study involving 10,539 individuals suggested that the association between TSH and MAFLD was mediated by the characteristics of MetS (waist circumference, HDL levels, triglycerides levels, DM, and systemic arterial hypertension) ( 33 ). Notably, an inverse correlation between FT4 level and risk were found in some studies ( 12 , 29 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…HYPOTHYROIDISM is a metabolic disease which is characterized by low level of thyroid hormone (TH) and high level of thyroid-stimulating hormone in serum [1]. TH plays an important role in regulating lipid and glucose metabolism and insulin signaling [2][3][4]. According to previous literature, TH stimulates cholesterol and other lipid synthesis, increases mobilization of plasma cholesterol and triglycerides (TG) [5][6][7].…”
mentioning
confidence: 99%
“…After applying inclusion and exclusion criteria, 44 full-text articles were found to be potentially eligible. Of these, 10 articles [ 15 - 24 ] were identified as suitable to the aims of our research question and met the quality specifications necessary for this systematic review.…”
Section: Reviewmentioning
confidence: 99%
“…All of these studies were published between 2011 and 2021. The following studies were included: Janovsky et al [ 15 ], Tahara et al [ 16 ], Wang et al [ 17 ], Bano et al [ 18 ], Eshraghian et al [ 19 ], Gökmen et al [ 20 ], Lee et al [ 21 ], Ludwig et al [ 22 ], Mazo et al [ 23 ], and Shi et al [ 24 ]. Five of these studies were conducted in Asia, two in South America, two in Europe, and one in the Middle East.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation